2021
DOI: 10.3389/fonc.2021.593449
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Treatment of Radiation-Induced Brain Necrosis: A Systematic Review

Abstract: BackgroundRadiation brain necrosis (RBN) is a serious complication in patients receiving radiotherapy for intracranial disease. Many studies have investigated the efficacy and safety of bevacizumab in patients with RBN. In the present study, we systematically reviewed the medical literature for studies reporting the efficacy and safety of bevacizumab, as well as for studies comparing bevacizumab with corticosteroids.Materials and MethodsWe searched PubMed, Cochrane library, EMBASE, and ClinicalTrials.gov from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(78 citation statements)
references
References 76 publications
0
77
0
Order By: Relevance
“…The treatment of RN is a challenging issue as the number of RN patients has gone up with the widespread application of radiotherapy over the last decades. Corticosteroids and bevacizumab are the two main recommended treatments ( 13 , 14 ). Corticosteroids are the first-line treatment for RN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of RN is a challenging issue as the number of RN patients has gone up with the widespread application of radiotherapy over the last decades. Corticosteroids and bevacizumab are the two main recommended treatments ( 13 , 14 ). Corticosteroids are the first-line treatment for RN.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are the first-line treatment for RN. A recent review summarized that bevacizumab was more efficacious than corticosteroid treatment ( 13 ). Interestingly, our study found that the treatment strategy combining bevacizumab with corticosteroids did not lead to better clinical outcomes for NPC patients with RN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients requiring longer term treatment, bevacizumab (an anti-vascular endothelial growth factor (VEGF) monoclonal antibody) has demonstrated robust clinical and radiographic response in multicenter prospective trials, avoiding steroid-treatment toxicity ( 61 , 62 ). Bevacizumab has also shown significant improvement in neurocognitive outcomes, including attention, language, concentration, memory, visuospatial orientation, and calculation at two months compared to patients treated with corticosteroids only ( 63 ). However, as an anti-angiogenesis agent, bevacizumab decreases wound healing and predisposes patients to hemorrhage and thrombosis.…”
Section: Traditional Therapiesmentioning
confidence: 99%
“…Extrinsic factors consist of physical and biological barriers preventing trafficking of therapies into the intracranial space, such as the blood brain barrier and tumor microenvironment ( 65 ). For immunotherapies like CAR T-cell and virotherapies, intrinsic limitations such as limited targetable tumor antigens, insufficient proliferation or expansion and lack of durable response can also hinder clinical efficacy ( 63 ). Brain tumors, especially gliomas, can circumvent the binding and targeting of these novel therapies by upregulating expression of inhibitory ligands and cytokines, and downregulating targeted tumor antigens, preventing recognition by CAR T-cells, viral vectors, and avoiding check point inhibition ( 68 , 69 ).…”
Section: Novel Therapiesmentioning
confidence: 99%